Untargeted metabolomics fingerprints in seminal plasma of patients with abnormal sperm morphology using high-performance liquid chromatography and mass spectrometry - Serena Correnti; Giuseppina Fanelli; Mariaimmacolata Preianò; Veronica Lelli; Mariagrazia Tarantino; Annalisa Fregola; Massimo Bitonti; Emanuela Chiarella; Anna Maria Timperio; Sara Rinalducci; Rocco Savino; Rosa Terracciano (Frontiers in Molecular Biosciences)
Teratozoospermia, a qualitative sperm disorder characterized by abnormal sperm morphology, represents one of the causes of male infertility worldwide. The metabolic analysis of human seminal plasma (SP), can provide insights into the underlying molecular mechanisms of this condition, identifying novel biomarkers and facilitating the development of diagnostic tests. In this study, an untargeted High-Performance Liquid Chromatography-Mass Spectrometry (HPLC-MS) approach was performed to explore SP metabolic alterations associated with teratozoospermia. SP samples from 15 teratozoospermic (TZ) vs. 20 normozoospermic (NZ) subjects were analyzed to identify metabolic pathways linked to sperm morphology dysfunction. Multivariate statistical analysis, including Partial Least Squares Discriminant Analysis (PLS-DA) and Orthogonal PLS-DA, revealed a distinct separation between TZ and NZ, highlighting 14 significantly altered metabolites. Based on Variable Importance in Projection scores, O-acetyl-L-serine showed the highest score. Main findings include alterations in Creatine, Histidine, Adenine, Allantoin and Deoxyuridine levels, suggesting perturbations in inflammation, oxidative stress and sperm DNA damage in teratozoospermia. Correlation and Receiver Operating Characteristic (ROC) analyses identified potential biomarkers, including O-acetyl-L-serine, Creatine, and Histidine, with robust discriminatory power (AUC >0.7). These findings highlight potential metabolic pathways implicated in the pathophysiology of teratozoospermia and provide a foundation for enabling personalized patient management with precision treatment.